Carbon rationing and personal energy use (Multi-Science Publishing, 2004)
A new policy approach is needed to deliver carbon dioxide savings in the UK; this paper proposes carbon rationing for personal energy use. Current policies are extremely unlikely to result in sufficient savings to meet the 2010 national reduction target. Indeed, when international air travel emissions are included, carbon equivalent emissions have not actually fallen since 1990. In the domestic sector, energy efficiency is expected to deliver significant carbon savings, but data from recent decades show this to be a triumph of hope over experience. Instead carbon rations for personal transport and household energy use are suggested. Rations would be equal, tradable, mandatory and would decrease year-on-year. The aim would be to make guaranteed carbon savings in an egalitarian way. Practical details of rationing are outlined and concerns about its effects are debated. Finally, it is concluded that rationing has great potential to enable the UK, and other countries, to meet their carbon saving targets.